Method and application of preparing high microporous NaY molecular sieve with the aid of terminal alcohol compound

The preparation of high-microporous NaY molecular sieve through end alcohol compounds assisted in the preparation of high-microporous NaY molecular sieve solved the economic and environmental sustainability problems of the existing technology in deep removal of low concentrations of SO2, achieved efficient and reversible SO2 adsorption effect, and simplified the preparation process. Suitable for industrial applications.

CN116534869BInactive Publication Date: 2024-12-27FUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310479997.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-28
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has economic and environmental sustainability problems in deep removal of low concentrations of SO2. Traditional methods such as limestone method and ionic liquid solvents will corrode the equipment during the regeneration process and the by-products are difficult to recover. The commonly used zeolite preparation methods use expensive template agents, limiting their industrial applications.

Method used

The high specific surface area and microporous pores were prepared by mixing silicon source, aluminum source and sodium source with terminal alcohol compound surfactants at room temperature and hydrothermal crystallization was carried out to prepare high specific surface area and microporous pores. Large NaY molecular sieve in volume is used for efficient adsorption of SO2.

Benefits of technology

It realizes efficient dynamic adsorption of SO2 at room temperature and pressure. The resulting NaY molecular sieve has a high crystallinity, an adsorption rate of more than 90%, and the preparation method is simple, green and economical, suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116534869B_ABST
    Figure CN116534869B_ABST
Patent Text Reader

Abstract

The present invention discloses a method and application of preparing a high microporous NaY molecular sieve with the aid of a terminal alcohol compound, and belongs to the technical field of material preparation and environmental purification. The method uses an aluminum source, a silicon source, and a sodium source as raw materials, adds a terminal alcohol compound surfactant, and undergoes hydrothermal crystallization to prepare the high microporous NaY molecular sieve. The NaY molecular sieve prepared by the present invention has high crystallinity, a large specific surface area, and a large micropore volume. It can be used as an adsorbent to efficiently adsorb SO2 gas at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of material preparation and environmental purification, and relates to a preparation technology of a NaY molecular sieve adsorbent and its application, and specifically to a method for preparing a high-microporous NaY molecular sieve with the aid of a terminal alcohol compound and its application in deep removal of SO2. Background Art

[0002] Sulfur dioxide (SO2) is a byproduct of fuel combustion and is emitted into the atmosphere. The flue gas usually contains about 500-3000ppm of SO2, which not only greatly aggravates air pollution and easily induces human respiratory diseases, but also seriously hinders industrial production. All factories have strict requirements for deep desulfurization. Since the absorption capacity of SO2 is very small, removing SO2 at low concentrations makes deep desulfurization a huge challenge.

[0003] Traditionally, the limestone method commonly used in industrial wet flue gas desulfurization (Fuel, 2015, 144, 274-286) can effectively remove SO2, but it will produce a large amount of wastewater and residues, corrode pipelines, and require further treatment. Although ionic liquid solvents (Chem. Eng. J., 2015, 265, 249-258.) can effectively absorb SO2 without accumulating secondary solid waste, they will not only corrode equipment during the regeneration process, but also the solvent will be easily lost, which fundamentally and severely limits this process. In general, dry desulfurization is currently the most practical, economical and effective technology for eliminating sulfur-containing pollutants in industry. A large number of solid adsorbents including metal oxides, activated carbon and zeolites have been developed for capturing sulfur compounds. Metal oxide (J. Hazard. Mater., 2018, 342, 326-334.) adsorbents are expensive and produce additional unusable metal sulfate byproducts. For activated carbon (Energy Fuels, 2021, 35, 8102-8116), its high regeneration cost restricts its development. In general, these technologies are seriously affected by economic and environmental sustainability issues. Therefore, there is an urgent need to develop adsorbent materials with excellent adsorption performance, regeneration, and easy product recovery for efficient and reversible SO2 capture.

[0004] Zeolites have been at the forefront of many studies. Zeolites have a large specific surface area and adjustable porosity, and can effectively screen and separate mixed gases through differences in adsorption and diffusion. At the same time, zeolites have high adsorption performance, excellent reusability and continuous regeneration ability, and relatively low reaction temperature. NaY molecular sieve is a silicon aluminum phosphate crystal. Due to its unique crystal structure, uniform and regular micropore channels, large specific surface area and excellent thermal stability, it is widely used in petrochemicals, energy, environmental governance and other fields. NaY zeolite has a wide pore distribution, large pore size, and low mass transfer resistance. It is a highly potential adsorbent that is conducive to the efficient adsorption of low-concentration SO2 and high-cycle adsorption regeneration. Generally, the template required for the preparation of zeolites is expensive, and most zeolites are still in the laboratory stage and have not been industrialized.

[0005] At present, the use of surfactants to prepare NaY zeolite has been reported. For example, patent CN 103449469A adds surfactants to the synthesis of directing agents to obtain NaY zeolite with good stability. Patents CN 102259889A and CN 103214003A respectively disclose the use of N, N-diethylamino-N-hexadecyl-N-(3-methoxypropane) ammonium iodide and N, N-dimethyl-N-[3-(trimethoxysilyl)propyl] octadecyl ammonium chloride (TPOAC) amphiphilic organosilane as templates to synthesize Y zeolite. However, the above method uses expensive organosilane as a template, which is used in a large amount and takes a long time to crystallize, which will undoubtedly greatly increase the synthesis cost of multi-level pore Y molecular sieves and is not conducive to its industrial application and promotion. Therefore, it is very important to design a simple and green strategy for the rapid synthesis of NaY molecular sieves. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a high microporous NaY molecular sieve with the aid of a terminal alcohol compound and its application. The NaY molecular sieve prepared by this method has good crystallinity, a large specific surface area and a high micropore volume, and can achieve efficient dynamic adsorption of SO2 at room temperature and pressure.

[0007] To achieve the above object, the present invention adopts the following technical solution:

[0008] A method for preparing a high-microporous NaY molecular sieve using a terminal alcohol compound as an auxiliary, comprising the following steps:

[0009] 1) Add water to mix silicon source, aluminum source and sodium source, then add appropriate amount of terminal alcohol compound surfactant, and stir at room temperature to make the materials fully contact;

[0010] 2) transferring the material obtained in step 1) into a Telfon reactor and placing it in an oven for hydrothermal crystallization;

[0011] 3) After the Telfon reactor is cooled, the solid product obtained after the crystallization in step 2) is washed with deionized water until it is neutral, and then centrifuged, filtered, and dried to obtain the high microporous NaY molecular sieve.

[0012] Furthermore, the aluminum source in step 1) is sodium aluminate (NaAlO2).

[0013] Furthermore, the silicon source in step 1) is silica sol.

[0014] Furthermore, the sodium source in step 1) is at least one of sodium aluminate (NaAlO2) and sodium hydroxide (NaOH).

[0015] Furthermore, the terminal alcohol compound surfactant in step 1) is a surfactant of a straight-chain or branched alkane with a terminal alcohol group and 2-6 carbon atoms, which is specifically at least one of methanol, ethanol, propanol, butanol, pentanol, hexanol, ethylene glycol, and polyethylene glycol.

[0016] Furthermore, the molar ratio of the silicon source (calculated as SiO2), sodium source, aluminum source (calculated as Al2O3) and water used in step 1) is (0.01-0.025):(0.003-0.004):(0.004-0.01):(0.3-0.4); the molar ratio of the terminal alcohol compound surfactant used to the silicon source (calculated as SiO2) is 0.1-0.6.

[0017] Furthermore, in step 2), the hydrothermal crystallization temperature is 80-120° C. and the time is 6-24 h.

[0018] Furthermore, the drying temperature in step 3) is 70-100°C and the drying time is 8-12 h.

[0019] The specific surface area of ​​the highly microporous NaY molecular sieve prepared above is 616~690 m 2 / g, and the micropore volume is 0.32~0.34 cm 3 / g, which can be used as an adsorbent for the adsorption and removal of SO2.

[0020] The significant advantages of the present invention are:

[0021] The preparation method of the present invention is simple, green, economical, energy-saving and efficient. The obtained NaY molecular sieve has high crystallinity, large specific surface area and large micropore volume, and can achieve efficient adsorption of SO2 gas under normal temperature and pressure conditions. After being recycled for 15 times, the adsorption rate of SO2 can still be maintained at more than 90%. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The XRD spectra of the molecular sieve samples prepared in Examples 1-4 are shown.

[0023] Figure 2 The pore size distribution diagram of the molecular sieve samples prepared in Examples 1-4.

[0024] Figure 3 This is a diagram showing the N2- adsorption and desorption of the molecular sieve samples prepared in Examples 1-4.

[0025] Figure 4 The SO2 dynamic adsorption curve of the molecular sieve samples prepared in Examples 1-4.

[0026] Figure 5 This is a graph showing the SO2 adsorption capacity of the molecular sieve samples prepared in Examples 1-4.

[0027] Figure 6 This is a graph showing the SO2 adsorption capacity of the molecular sieve samples prepared with PEG of different molecular weights in Example 5. DETAILED DESCRIPTION

[0028] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0029] Example 1

[0030] The NaY molecular sieve is synthesized by a hydrothermal method, which specifically includes the following steps:

[0031] Weigh 0.004 mol NaAlO2 and add it to a solution consisting of 0.004 mol g NaOH and 0.3 mol deionized water, then add 0.02 mol silica sol and stir at room temperature for 2 h to allow the components to fully contact and obtain the initial gel. Transfer the initial gel into the Telfon kettle lining, put the kettle into an oven, and hydrothermally crystallize at 100 °C for 12 h. After the crystallization, wash, filter and dry the solid product at 80 °C for 8 h. The prepared molecular sieve sample is named pristine Y.

[0032] Example 2

[0033] Before adding the silica sol, n-pentanol equivalent to 0.2 times the molar amount of SiO2 in the silica sol was additionally added as a surfactant. Other operations were the same as those in Example 1. The prepared molecular sieve sample was named PeOH-Y.

[0034] Example 3

[0035] Before adding the silica sol, ethylene glycol equivalent to 0.2 times the molar amount of SiO2 in the silica sol was additionally added as a surfactant. Other operations were the same as those in Example 1. The prepared molecular sieve sample was named EG-Y.

[0036] Example 4

[0037] Before adding the silica sol, PEG-4000 equivalent to 0.2% of the molar amount of SiO2 in the silica sol was additionally added as a surfactant. Other operations were the same as those in Example 1. The prepared molecular sieve sample was named PEG4000-Y.

[0038] Example 5

[0039] The PEG-4000 used in Example 4 was replaced by an equal molar amount of PEG-400, PEG-1000 or PEG-2000, and the other operations were the same as in Example 4 to prepare the corresponding molecular sieve samples.

[0040] Figure 1 The XRD spectra of the molecular sieve samples prepared in Examples 1-4 are shown. As can be seen from the figure, the characteristic peaks of the molecular sieve sample synthesized in Example 1 are basically consistent with those of the PDF standard card (JCPSD NO.43-0168) of pure NaY, and the samples synthesized by adding n-pentanol, ethylene glycol and polyethylene glycol are also basically consistent with the characteristic peaks of pure NaY, and their crystallinity is higher than that of the pure NaY sample. This proves that the addition of terminal alcohol compound surfactants can directly prepare pure phase NaY molecular sieves, among which the sample obtained in Example 4 has the highest crystallinity.

[0041] Figure 2 The pore size distribution diagram of the molecular sieve samples prepared in Examples 1 to 4 shows that the introduction of the terminal alcohol compound better preserves the microporous structure of NaY.

[0042] Table 1 shows the texture properties of the molecular sieve samples prepared in Examples 1-4 of the present invention.

[0043] Table 1 Structural parameters of the samples in the examples

[0044]

[0045] As shown in Table 1, the specific surface area and micropore volume of the NaY sample synthesized without adding the terminal alcohol compound in Example 1 (Example 1) are only 585 m 2 / g and 0.29 cm 3 / g. The molecular sieve sample synthesized by introducing n-pentanol (Example 2) has a specific surface area and micropore volume of 672 m 2 / g and 0.32 cm 3 / g, indicating that n-pentanol molecules have the ability to construct NaY molecular sieve micropores. The molecular sieve sample synthesized by introducing ethylene glycol additive (Example 2) has a specific surface area and micropore volume of 616m 2 / g and 0.32 cm 3 / g, indicating that ethylene glycol molecules have the ability to construct NaY molecular sieve micropores. Compared with the samples of Examples 1-3, the molecular sieve sample synthesized in Example 4 has a specific surface area and micropore volume as high as 690 m2 under the condition of using only 0.2 mol% polyethylene glycol. 2 / g and 0.34 cm 3 / g, which is significantly greater than that of other samples, indicating that polyethylene glycol molecules can greatly enhance their ability to induce molecular sieves to construct micropores during synthesis, and also that terminal alcohol compounds have the ability to induce NaY molecular sieves to form micropores.

[0046] SO2 adsorption test: At room temperature and pressure, 0.10 g of the molecular sieve sample prepared in Example 1-4 was taken, and the SO2 gas concentration was 1000 ppm, N2 was the balance gas, and the raw material gas flow rate was 40 mL·min -1 , mass space velocity is 24000 mL·g -1 ·h -1 SO2 adsorption was evaluated under the conditions of .

[0047] When the molecular sieve sample is used for SO2 adsorption, the calculation formula for its breakthrough amount and adsorption saturation amount is as follows:

[0048] ,

[0049] .

[0050] Figure 3 The N2 adsorption-desorption spectra of the molecular sieve samples prepared in Examples 1 to 4. According to the IUPAC classification, all samples show a type I adsorption isotherm, that is, they all have a microporous structure with good selectivity.

[0051] Figure 4 The following is a graph showing the dynamic adsorption of SO2 by the molecular sieve samples prepared in Examples 1-4. From the results of adsorption, it can be seen that the NaY prepared by introducing the terminal alcohol compound has a higher adsorption of SO2. From the perspective of penetration time, compared with the original NaY molecular sieve, the penetration time of the molecular sieve synthesized by adding the terminal alcohol compound is significantly prolonged, especially the penetration time of the PEG-Y molecular sieve is 2.3 times that of the original NaY.

[0052] Figure 5 Figure 1 is a graph of the SO2 adsorption of the molecular sieve samples prepared in Examples 1-4. Figure 5 It can be seen that the molecular sieves synthesized by adding terminal alcohol compounds have improved SO2 capture capacity, among which the SO2 capture capacity of PEG-Y molecular sieve reaches 314 mg / g.

[0053] Figure 6 Figure 5 shows the SO2 adsorption of the molecular sieve samples prepared by different molecular weight PEG. Figure 6 It can be seen that with the increase of PEG molecular weight, the SO2 capture ability of the prepared molecular sieve gradually improves, among which the SO2 adsorption capacity of PEG4000-Y molecular sieve is the highest.

[0054] In summary, the NaY molecular sieve prepared by the present invention has a simple process, has excellent performance in the adsorption and removal of SO2, and has good cycle stability, and has great application potential.

[0055] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing high microporous NaY molecular sieve using terminal alcohol compounds, characterized in that: The following steps are involved: 1) Add water to the silicon source, aluminum source and sodium source, then add an appropriate amount of terminal alcohol compound surfactant, and stir at room temperature to allow the materials to fully contact; 2) subjecting the material obtained in step 1) to hydrothermal crystallization; 3) washing the solid product obtained after the crystallization in step 2) with deionized water until it is neutral, and then centrifuging, filtering and drying to obtain the high microporous NaY molecular sieve; The molar ratio of the silicon source, sodium source, aluminum source and water used in step 1) is (0.01-0.025):(0.003-0.004):(0.004-0.01):(0.3-0.4); the molar ratio of the terminal alcohol compound surfactant used to the silicon source is 0.1-0.6; the terminal alcohol compound surfactant is at least one of methanol, ethanol, propanol, butanol, pentanol, hexanol, ethylene glycol, and polyethylene glycol; The hydrothermal crystallization temperature in step 2) is 80-120°C and the time is 6-24 h.

2. The method for preparing high microporous NaY molecular sieve using terminal alcohol compounds as an aid according to claim 1, characterized in that: The aluminum source in step 1) is sodium aluminate.

3. The method for preparing high microporous NaY molecular sieve using terminal alcohol compounds as an aid according to claim 1, characterized in that: The silicon source in step 1) is silica sol.

4. The method for preparing high microporous NaY molecular sieve using terminal alcohol compounds as an aid according to claim 1, characterized in that: The sodium source in step 1) is at least one of sodium aluminate and sodium hydroxide.

5. The method for preparing high microporous NaY molecular sieve using terminal alcohol compounds as an aid according to claim 1, characterized in that: The terminal alcohol compound surfactant in step 1) is a surfactant of a straight-chain or branched alkane with a terminal alcohol group and 2 to 6 carbon atoms.

6. The method for preparing high microporous NaY molecular sieve using terminal alcohol compounds as an aid according to claim 1, characterized in that: The drying temperature in step 3) is 70-100°C and the drying time is 8-12 h.

7. A high microporous NaY molecular sieve prepared by the method of claim 1, characterized in that: The specific surface area of ​​the molecular sieve is 616~690 m 2 / g, and the micropore volume is 0.32~0.34 cm 3 / g.

8. Use of the high microporous NaY molecular sieve as claimed in claim 7 in the adsorption removal of SO2, characterized in that: Under normal temperature and pressure conditions, the high microporous NaY molecular sieve is used as an adsorbent for adsorbing SO2 gas.